Engineering mechanics dynamics Ed 8 Vol 1 - Meriam J L; Kraige L G; Bolton J N (New Delhi Wiley, 2023)
The book comprises previous years$1 (B(2000 to 2020) GATE questions in Electronics and Communication Engineering covered Chapter-wise with detailed solutions. Each Chapter begins with a detailed year-wise analysis of topics on which questions are based and is followed by listing of important Formulas and concepts for that Chapter the book is designed to make the students well-versed with the pattern of examination, level of questions asked and the concept distribution of questions and thus bring greater focus to their preparation. It aims to be a must-have resource for an essential step in their preparation, that is, solving and practicing previous years$1 (Bpapers.s
Keywords: SI Version; Force Systems; Equilibrium; Distributed Forces